Impact of elevation and slope aspect on floristic composition in wadi Elkor, Sarawat Mountain, Saudi Arabia - Mohamed A. Fadl (Nature Portfolio, 2021)
Abstract The current research was carried out in Wadi Elkor, one of the Sarawat Mountains regions, which is a special location from an environmental standpoint and one of the only places in Saudi Arabia where a range of Palaearctic flora co-exists with Afrotropical species. The study aimed to determine the floristic composition as well as the effects of slope aspect and elevation on species, life forms, and phytogeographical elements distribution. The study area is located in Wadi Elkor, a valley in the Sarawat Mountains that cuts off the Al-Hada escarpment, 47 km southeast of Makkah City, Saudi Arabia. We conducted the research at three different locations, each with a different elevation and slope aspect. Based on floristic composition, Ward classification moreover Jaccard comparisons were performed. A total of 189 species was discovered, divided into 131 genera and 43 families. The current study identified Argyrolobium rarum Dumme as a new vascular plant in Saudi Arabia's terrestrial flora. In the current study, the Gramineae, Leguminosae, and Compositae families contributed 29% of the total plant species, whereas 14 families were represented by one species each. Solanum was the most numerous genus, with seven species, followed by Acacia and Pulicaria, each with six species, while Commicarpos and Euphorbia, each with four species. At an elevation of 1060 m above sea level, the north facing slope had the most plants, genera, and families. Therophytes had the most species, accounting for 44%, followed by Chamaephytes, which accounted for 26%. Hemicryptophytes accounted for 12% of the total, while phanerophytes accounted for 10%. In the studied area, the bioregional Saharo-Sindian and Sudano-Zambesian groups were the most well-represented (41%). The floristic composition, as well as the distribution of life forms and phytogeographical components, were found to be significantly affected by the elevation and slope aspects. The study showed that slope aspect and elevation both affected the distribution of plant species, with elevation being the most influential of the two variables.